Erroneous analysis in English writing assessments among undergraduates in a public university / Nurul Akmal Awang and Nurain Jantan Anua Jah - Awang, Nurul Akmal; Jantan Anua Jah, Nurain (Universiti Teknologi MARA, 2022)
A number of studies on morphological error analysis have been carried out in different settings, contexts, and levels of study to observe, analyze and describe the errors correlated to English grammar rules. Based on the Surface Strategy Taxonomy by Dulay et al. (1982), this current study focused on the investigation of the types and factors of errors in English writing assessment specifically among undergraduates in a public university in Malaysia. This current study employed a qualitative research method by using a case study. 30 samples of English writing assessment were analyzed based on the taxonomy and the framework of Source s of Errors by Richard (1974). The findings revealed that the students committed a total of 248 errors on 30 transcripts; 95 were Omission errors, 91 were Misformation errors, 54 were Addition errors and only 8 were Misordering errors. Thus, the findings highlighted that Omission was recorded as the top error committed by learners followed by Misformation, Addition and lastly, Misordering. As for the source of error, Intralingual error was marked as the most prevalent factor contributed to the errors. The outcome of the study may shed some light on emphasizing the possible interventions to assist learners in their writing as well as developing a remedial programme to help learners to master English grammar.